« Manœuvrer en douceur ». Traduction et philologie des textes politiques : la Monarchie de Dante - Diego Quaglioni (Laboratoire Italien)
A new translation of the Dante’s Monarchy (1313) may be a stand as a good example of research on how to read and interpret medieval and early-modern political texts. The treaty conceived by Dante is one of the most important contributions to the development of the vocabulary of politics in the West, through the modern translations like those of Marsilio Ficino (1468) and Johannes Basilius Herold (1559). Each translation that proposes to “reawaken the echo of the original” (Walter Benjamin) is the expression of “posthumous maturity” of the political text, provided that it manages to not overlap with it: the warning of André Pézard, the greatest French interpreter of Dante’s works, reads: “Handle with care”. The translator’s task is therefore to that of “diagonalize” the whole history of the translations of a political text, because the translation is, in a form that renews itself constantly, the last stage of his life.